Solid Dissolution and Liquid Mixing in Turbulent Stirred Tanks. Issue 8 (8th May 2019) - Montante, Giuseppina; Carletti, Claudio; Maluta, Francesco; Paglianti, Alessandro
Abstract: The dissolution of salt particles in turbulent stirred vessels is investigated. A novel method for achieving the simultaneous identification of the liquid mixing time and the dissolution time of salt particles from the conductivity data collected by electrical resistance tomography is presented. The characteristic time of the liquid mixing during the dissolution is found to be either uninfluential or significant on the dissolution itself, depending on the salt particle diameter and the vessel size. The adoption of a combination of literature correlations, which are proved to adequately estimate the two times, is suggested as a simple tool for identifying the minimum particle size for optimizing the dissolution operation. Abstract : A novel method for the simultaneous identification of the liquid mixing time and the dissolution time of salt particles in stirred vessels is presented. During the dissolution, the time required for the liquid blending is found to be either uninfluential or significant on the total time required for the operation accomplishment, depending on the salt particle diameter and the vessel size.